THE INFLUENCE OF OPERATIONAL COSTS (BOPO), THIRD PARTY FUNDING PROFIT SHARING (DPK), AND CASH RATIO ON PROFITABILITY WITH MURABAHAH FINANCING AS A MODERATION VARIABLE IN SUMUT SHARIAH BANK - Azzahra, Maylin; Fadhila Rahma, Tri Inda; Bi Rahmani, Nur Ahmadi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Profitability is a company's expertise in generating margins or profits as long as the company operates. Financing at Bank Sumut Syariah can be considered as one of the driving factors for increasing the profitability of a bank. It's just that the financing contained in Bank Sumut Syariah does not fully affect profitability, but other factors that most affect the profitability of the bank. The purpose of this research is to show whether Operational Costs (X1), Profit Sharing of Third Party Funds (X2) and also Cash Ratio (X3) have an influence on profits or profit (Y) with Murabahah Financing (Z) as a moderating variables. For this reason, the researchers here used the SEM analysis research method and Bootstrapping using SMARTPLS with secondary data and the nature of the quantitative research used in testing the data that had been obtained at Bank Sumut Syariah. In this study, the results obtained were that the variables BOPO (X1), DPK (X2), CR (X3) and also Murabahah Financing (Z) did not have a relevant impact on Profitability (Y) of PT Bank Sumut Syariah which had been processed and conclusions drawn from several tests that have been carried out. Then it was also obtained from the research that the Murabahah Financing itself weakened the relationship between DPK and ROA. And also Murabaha financing weakens the relationship between CR and ROA. However, Murabahah Financing strengthens the relationship between BOPO and ROA. So it can be said that Murabahah Financing moderates the effect of BOPO on ROA. However, Murabahah Financing cannot moderate the effect of TPF on ROA nor can it moderate the effect of CR on ROA. Keywords: Operating Costs, Profit Sharing Of Third Party Funds And Cash Ratios To Profitability